Characteristics and needs of long-stay forensic psychiatric inpatients: a rapid review of the literature - Huband, Nick; Furtado, Vivek; Schel, Sandra; Eckert, Mareike; Cheung, Natalie; Bulten, Erik; Völlm, Birgit (Taylor & Francis, 2018)
This rapid review summarises currently available information on the definition, prevalence, characteristics and needs of long-stay patients within forensic psychiatric settings. Sixty nine documents from 14 countries were identified. Reports on what constitutes ‘long-stay’ and on the characteristics of long-stay patients were inconsistent. Factors most frequently associated with longer stay were seriousness of index offence, history of psychiatric treatment; cognitive deficit, severity of illness, diagnosis of schizophrenia or psychotic disorder, history of violence, and history of substance misuse. Although some countries are developing specific long-stay services, there is presently no consensus on what might constitute ‘best practice’ in such settings.